Сонячний контролер заряду на базі Arduino - Слюсаренко, О. А.; Карнаушенко, В. П. (ХНУРЕ, 2019)
Solar System is now used for green energy generation. However there arises a problem in voltage levels which affects the system stability. As the solar cell generates fewer amounts of charges we have to use a controller to maximize the efficiency. In this project MPPT (Maximum power point tracker) method is developed with LM324 comparator with optocoupler. The results are taken from wireless technique of Bluetooth module and a display panel interfacing with Arduino UNO. This system protects the battery from over charging and deep discharging to increase battery life.
Keywords: Сонячний контролер заряду; Arduino